Designing Home Security With Esp32-Cam and IoT-Based Alarm Notification Using Telegram - Hery Kurniawan; Susanto Hariyanto (Komunitas Dosen Indonesia, 2023)
Nowadays, technological advances have entered human life. One of the security system solutions is the use of Closed Circuit Television (CCTV) as a monitoring medium, but it is still lacking. This is because more and more crimes are committed in homes where the owner is away. As a result, each home needs a security system that can protect the wealth and assets of the owner. Similarly, currently existing security systems are rarely able to provide data directly to homeowners if an outsider wants to commit a crime. So, research was conducted with the title